(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Several previous studies have revealed that some of the teachers of the integration special education program (PPKI) do not have skills in managing their assignments. In addition, they are also said not to do adequate preparation in performing tasks. There are also studies that state that the level of readiness of PPKI teachers in performing tasks is still low. The preparation done by the teachers allows them to manage the workload well. Adequate readiness can also ensure efficient task management. It is also an important impetus in avoiding the occurrence of teacher workload. This qualitative study was conducted to detail the elements of teacher readiness in the construct of workload of special education teachers. This study involved 11 PPKI coordinators in the state of Johor, Malaysia as respondents for the interview session. The findings of this study can be used as a basic reference for future researchers in providing exposure related to the readiness of special education teachers.